Shifting invertebrate distributions in the Barents Sea since pre-1900 - Calvet, Nathalie; Bluhm, Bodil A.; Yoccoz, Nigel Gilles; Altenburger, Andreas (Frontiers in Marine Science, 2024)
Marine invertebrate habitats are experiencing warming, and oceanic carbon dioxide levels are on the rise. These changes result in shifts in species distributions. Monitoring and understanding these shifts provides vital information because each species plays a unique ecological role, and the human utilization of marine species is intrinsically linked to their geographic locations. Here, we examine distribution shifts of marine invertebrates in the Barents Sea since pre-1900. Using data from the Global Biodiversity Information Facility, we analyzed species occurrences across warm, cold and mixed temperature zones, distinguishing between benthic and pelagic taxa. Our findings indicate community shifts in each of five separated time periods, with the most pronounced shifts occurring after 1980 in the cold and mixed zones, and earlier in the warm zone. The significant biogeographical changes at the community scale occurred both in benthic and pelagic realms, yet with differing trajectories in the period past 2000, and largely coincided with increased Atlantic Water inflow and reduced ice cover. Several invertebrate taxa exhibited a northward movement, falling into two categories: species migrating into the Barents Sea from the Norwegian mainland shelf, and those relocating from the southern Barents Sea to areas with mixed and colder temperatures. Some of these species may serve as indicator species for monitoring ecosystem and community change. The study highlights the importance of long-term datasets in quantifying community distribution shifts and understanding their ecological impacts.